Evaluation of the influence of the polymer-filler interaction on compounds based on epoxidized elastomeric matrix and precipitated silica - Tatiana L. A. C. Rocha; Marly M. Jacobi; Dimitrios Samios; Robert H. Schuster (Polímeros, 2006)
The introduction of epoxy groups into the main chain of elastomers has emerged as a promising alternative, considering the monitoring of polymer-filler interaction leading to changes in the properties of vulcanizates. The epoxidation reaction (in situ) was chosen to modify elastomers, such as polybutadiene (BR) and copolymer of styrene-butadiene-rubber (SBR), because it is a simple, easily controlled reaction, even considering the small epoxidation degree. The modification degree of the polymeric chain was studied with FT-IR and ¹H-NMR. The shift of the Tg to high temperatures with the increase of the epoxy group in the polymer chain was monitored through differential scanning calorimetry (DSC). An analysis of the dynamic modulus of the material in relation to its dependence on the amplitude and temperature was carried out. The interaction between epoxidized elastomeric matrix and silica as filler was extremely improved, even in the presence of very low content of epoxy groups into the polymer chain.